Characterization and Antibacterial Activity of the Natural Biopolymer Extracted from Pseudomonas aeruginosa - Al-Zaidi, Massooma H. H.; Al-Tamimi, Wijdan H.; Saleh, Afrodet A. (Scientific Journal of Medical Research, 2023)
Objective: This study aimed to extract, purify, characterize, and assess the antibacterial efficacy of the biopolymer extracted from Pseudomonas aeruginosa. Methods: The ice-cold 96% ethanol and isopropanol were used for biopolymer extraction. For protein precipitation, 60% ammonium sulfate was utilized. The solubility, chemical color reactions, fourier transform infrared spectroscopy (FTIR), ultraviolet (UV)-visible spectroscopy and high-performance liquid chromatography (HPLC) techniques were used for the characterization of the biopolymer. The antibacterial efficacy of the biopolymer against the pathogens isolated from bacterial vaginosis was evaluated using the broth microdilution method. Results: The extraction of biopolymer produced by P. aeruginosa with ice-cold 96% ethanol and isopropanol yielded 9.22 and 0.2 g/L, respectively, and could be successfully purified using 60% ammonium sulfate. The purified biopolymer exhibited solubility in distilled water. The color chemical reagents methods indicated the presence of monosaccharides, disaccharides, polysaccharides, and amino acids in the composition of the biopolymer. The carbohydrate average concentration of sugars in the samples was 1083.33 ?g/mL. The UV-vis spectra of the produced biopolymer showed an absorbance peak at 285 nm. FTIR spectra revealed the main functional groups of the examined biopolymer. The FTIR spectra of the biopolymer exhibited main absorption bands at 3257.48, 2924.42, 2858.63, 1743.60, 1616.00, 1417.07, and 817.00 cm?1. HPLC findings showed one clear peak indicating the purity of the produced biopolymer, with a peak absorbance of 145.930 mAU. Biopolymer showed the highest percentage of inhibition (98.3%) recorded against Bacillus cereus, followed by Staphylococcus haemolyticus (96.8%) at a concentration of 250 ?g /mL. Conclusions: This work concluded that P. aeruginosa is a potential biopolymeraccumulating bacteria and could be used for low-cost biopolymer production to combat bacteria that have developed antibiotic resistance.